2018
DOI: 10.1177/1099636218777966
|View full text |Cite
|
Sign up to set email alerts
|

Active damping of sound transmission through an electrorheological fluid-actuated sandwich cylindrical shell

Abstract: An exact model is proposed for sound transmission through a sandwich cylindrical shell of infinite extent that includes a tunable electrorheological fluid core, and is obliquely insonified by a plane progressive acoustic wave. The basic formulation utilizes Hamilton’s variational principle, the classical and first order shear deformation shell theories, the Kelvin–Voigt viscoelastic damping model (for the electrorheological fluid-core layer), and the wave equations for internal/external acoustic domains coupled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 76 publications
0
8
0
Order By: Relevance
“…Ahmadi et al [57] analyzed the effect of different models of carbon nanotube distribution on the variation of acoustic transmission of FGM carbon nanotube-reinforced composite cylindrical shells using FSDT. Hasheminejad et al [58] performed STL through a sandwich cylindrical shell with electrorheological fluid core. Fu et al [59] indicated the effects of gradient index, porosity volume fraction, and porosity distribution type on the variations of STL of a FG porous cylindrical shell under nonlinear thermal loading.…”
Section: Introductionmentioning
confidence: 99%
“…Ahmadi et al [57] analyzed the effect of different models of carbon nanotube distribution on the variation of acoustic transmission of FGM carbon nanotube-reinforced composite cylindrical shells using FSDT. Hasheminejad et al [58] performed STL through a sandwich cylindrical shell with electrorheological fluid core. Fu et al [59] indicated the effects of gradient index, porosity volume fraction, and porosity distribution type on the variations of STL of a FG porous cylindrical shell under nonlinear thermal loading.…”
Section: Introductionmentioning
confidence: 99%
“…Daneshjou et al (2018) applied a modal transfer matrix approach to study the effects of mean external and air gap flows on sound transmission through a double-wall thick cylindrical shell system based on the three-dimensional theory of elasticity. Hasheminejad et al (2020) used the sliding mode control (SMC) strategy for semi-active sound transmission control across an electrorheological fluid (ERF)-based sandwich cylindrical shell under oblique plane wave incidence.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, employing auxiliary interior sound sources (speakers) for low-frequency sound field cancellation in the active noise control (ANC) technique is rather bulky, intrusive, and expensive, where the structural vibrations essentially continue unaffected [6,7]. On the other hand, the inherent characteristics of smart piezoelectric materials [810], electro-rheological fluids (ERFs) [1113], and magneto-rheological (MR) materials [14,15] directly integrated into the conventional structures as control actuators, along with sophisticated control algorithms and high speed digital computing devices, have made them suitable candidates for active structural acoustic control (ASAC) in distributed parameter systems. Furthermore, by adopting a hybrid design philosophy, one can concurrently benefit from the diverse characteristics of various classes of conventional actuation/absorption mechanisms which cannot be realized by using a single type of actuator/absorber system alone (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…This will be accomplished, after rigorous development of the associated acousto-elastic model, by applying the computationally simple and intrinsically robust multi-input multi-output sliding mode control (MIMO-SMC) strategy [4648] to the hybrid smart composite system. This way, the vibroacoustic response of the hybrid structure can effectively be suppressed through smart variation of the damping/stiffness characteristics of the spatially distributed ERF-core layer [1113] in collaboration with the active uniform force piezoelectric actuator layer [34,49–51] according to the control commands. The proposed acousto-elastic model can be of great interest for sound control engineers seeking acoustic partitions with superior sound transmission loss characteristics [2,6,52].…”
Section: Introductionmentioning
confidence: 99%